Rotational levels of the (0 0 0) and (0 1 0) states of D216O from hot emission spectra in the 320–860 cm-1 region - Mellau G. Ch.; Mikhailenko S. N. Semen Nikolaevich; Starikova E. N.; Tashkun S. A.; Over H.; Tyuterev Vl. G. (2004, 2004)
Title screen